Assessment of beach morphological changes at Pantai Sepat - Muhammad Faizzudin Hakim, Md Fadil (2018)
Analysis of beach morphology can determine the profile or physical attributes of a beach and thus obtain information about the short term trends (accretion and erosion) of coastal area. The processes of erosion and accretion are further intensified with the presence of seasonal variations effects. The study area was conducted at Pantai Sepat, which located in district of Pekan, facing the South China Sea view. The study area can be categorized as natural sandy beach area. Unlike beaches which slope to the sea for a few meters and then suddenly drop deep, Pantai Sepat beach seems to slope very gradually toward the sea. Several beach profiles were monitored approximately every two weeks start from November 20, 2017 until March 28, 2018 by using a total station by collecting horizontal distance and vertical distance in one fixed straight line. The temporary benchmark was identified and referred to sea tidal before the works started to get a long distance during a low tide. The rain gauge was installed at the study area in UMP Pekan. Then, the recorded rainfall data was analysed in order to investigate the effect of rainfall patterns to beach morphological changes. From rainfall data, the total rainfall depth for period of the study (128 days) is 1573.9 mm with the maximum daily data was recorded as 256.2 mm on 12 January 2018 with 256.2 mm rainfall depth and about 60 days were recorded as no rainfall. For monthly rainfall distribution, January 2018 was recorded as the wettest month with rainfall depth 771.2 mm. Meanwhile, February 2018 was identified as the driest month with 19.7 mm rainfall depth. Based beach profiles analysis, the erosion process was occurred at the upper and middle part while the accretion process was occur at the lower part of the beach. The highest rate of erosion occurred on January 19, 2018 because of the highest of rainfall depth collected from January 1, 2018 until January 18, 2018 as much as 747 mm depth while the highest rate of accretion occurred on February 28, 2018 affected by the lowest of rainfall depth collected from February 15, 2018 until February 28, 2018 as much as 9.2 mm only. Sieve analysis test also was conducted to determine the size of distribution D50 every two weeks along the study period based on three different parts which is upper, middle and lower. The biggest size of particle is 0.28 mm at upper part on March 28, 2018 while the finest size of particle is 0.11 mm at lower part which is collected on December 4, 2017. As conclusion, beach profile at the study area was highly affected by the patterns of rainfall distribution which were significantly eroded during the wet period (December 2017 to January 2018) and accreted within dry period (February 2018 to March 2018). Meanwhile, for the particles size of the beach, D50 were shown the biggest size at the upper part and the finest at the lower part of the beach profile along the study period.